The Physical Location of Stripe Rust Resistance Genes on Chromosome 6 of Rye (Secale cereale L.) AR106BONE - Duan, Yanling; Luo, Jie; Yang, Zujun; Li, Guangrong; Tang, Zongxiang; Fu, Shulan (Frontiers in Plant Science, 2022)
It was reported that the chromosome 6R of rye (Secale cereale L.) carries stripe rust resistance gene Yr83, and the region with the candidate resistance gene(s) still needs to be narrowed down. This study confirmed that the chromosome 6RLAr derived from rye AR106BONE contains stripe rust resistance gene(s). A wheat-rye T6BS.6RLAr translocation chromosome, a wheat-rye small-segment translocation T6RLAr-6AS.6AL, and three kinds of deleted T6BS.6RLAr translocations, T6BS.6RLAr-1, T6BS.6RLAr-2, and T6BS.6RLAr-3, were identified. Translocations T6BS.6RLAr, T6BS.6RLAr-2, and T6RLAr-6AS.6AL were highly resistant to stripe rust and T6BS.6RLAr-1 and T6BS.6RLAr-3 were highly susceptible. The molecular markers specific to 6RL determined that the three regions of the 6RLAr arm from 732,999,830 bp to the telomere, from 735,010,030 to 848,010,414 bp, and from 848,011,262 bp to the telomere were deleted from T6BS.6RLAr-1, T6BS.6RLAr-2, and T6BS.6RLAr-3, respectively. T6BS.6RLAr-2 and T6RLAr-6AS.6AL contained the segment that was deleted in T6BS.6RLAr-3. Therefore, it can be concluded that about 37 Mb segment from 848,011,262 bp to the telomere carried stripe rust resistance gene(s), and it was smaller than that with the Yr83 gene. Gene annotation indicated that about 37 Mb region contains 43 potential resistance genes, and 42 of them are nucleotide-binding site and leucine-rich repeat (NBS-LRR)-like resistance protein genes. The results in this study narrowed down the size of the region with candidate stripe rust resistance gene(s) on the 6RL arm, and the T6RLAr-6AS.6AL is a promising small-segment translocation for improvement of wheat cultivars.